The Meanig of ‘Halal’ from the Perspective of Business Actors in the Post-BPJPH Era: A Qualitative Phenomenological Analysis - Utami, Sari (Institut Agama Islam Negeri Bone, 2025)
This research is a qualitative phenomenological analysis of the meaning of 'halal' from the perspective of business actors in Indonesia following the enactment of Law Number 33 of 2014 concerning Halal Product Assurance (UU JPH). This research focuses on the lived experiences and meaning-making of business actors after the certification authority shifted from the Indonesian Ulema Council (MUI) to the Halal Product Assurance Agency (BPJPH). Using a methodology focused on in-depth understanding, this report identifies a paradigm shift from a voluntary community initiative to a mandatory state mandate, and examines how the meaning of 'halal' has shifted from a mere religious obligation to a strategic economic asset. Key findings indicate a dissonance between the narrative of bureaucratic convenience used by the government and the practical realities on the ground, particularly for Micro, Small, and Medium Enterprises (MSMEs). This analysis concludes that while the new policy aims to protect consumers and increase global competitiveness, there is a risk of losing certification's legitimacy if fundamental issues related to the integrity of the process, particularly in self-declaration schemes, are not comprehensively addressed. This research provides strategic recommendations for regulators and stakeholders to bridge these organizations and build a sustainable and trusted halal ecosystem.